2015
DOI: 10.1186/1747-597x-10-1
|View full text |Cite
|
Sign up to set email alerts
|

PrEP in substance abuse treatment: a qualitative study of treatment provider perspectives

Abstract: ObjectivesTo examine substance abuse treatment providers’ views on engaging clients in Pre-exposure Prophylaxis (PrEP) care and research trials.MethodsThirty-six medical and counseling service providers in six New York City outpatient substance abuse treatment programs participated in semi-structured qualitative interviews. Thematic content analysis was conducted by three coders, independently.ResultsProviders’ perspectives toward PrEP were characterized by six salient themes: 1) Limited PrEP awareness. 2) Amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…In Italy, 70% of HIV specialists said they would prescribe PrEP, 64% to serodiscordant couples but also 56% to other people at risk, [67] while in Argentina, 40% would consider prescribing PrEP to serodiscordant couples and 35% to sex workers [82]. Medical and counselling service providers supported PrEP in outpatient drug treatment clinics [83]. …”
Section: Resultsmentioning
confidence: 99%
“…In Italy, 70% of HIV specialists said they would prescribe PrEP, 64% to serodiscordant couples but also 56% to other people at risk, [67] while in Argentina, 40% would consider prescribing PrEP to serodiscordant couples and 35% to sex workers [82]. Medical and counselling service providers supported PrEP in outpatient drug treatment clinics [83]. …”
Section: Resultsmentioning
confidence: 99%
“…The higher level of knowledge about PrEP in MSM may stem from a number of PrEP initiatives that have primarily focused on MSM and HIV seronegative partners in sero-discordant couples (Ware et al, 2012). Recent studies have also shown that many addiction treatment providers, with whom MMP patients are in daily contact, have limited awareness of PrEP (Shrestha et al, 2016; Spector et al, 2015). In the context of clinical settings, including MMP patients in this study, treatment providers have great potential to engage their at-risk clients about PrEP through counseling, referrals, research trials, and may also effectively promote adherence to PrEP through counseling and monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The suicide risk is greater in first or acute psychotic episodes, during the first six months after hospitalization [11, 12] and in SUD comorbid conditions [6, 8, 11, 1316]. Alcohol is one of the most studied substances since it has been shown to have a significant impact on suicide [1719] and cognition [20, 21]. Furthermore, DS patients, compared to SUD patients, are less motivated to change their consumption pattern, are more difficult to involve in treatment, exhibit slower progress, tend to give up long-term programs [22] and remain at risk of relapse even years after a period of full remission [23].…”
Section: Introductionmentioning
confidence: 99%